2004
DOI: 10.1016/j.str.2004.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Noncatalytic Assembly of Ribonuclease III with Double-Stranded RNA

Abstract: Ribonuclease III (RNase III) represents a family of double-stranded RNA (dsRNA) endonucleases. The simplest bacterial enzyme contains an endonuclease domain (endoND) and a dsRNA binding domain (dsRBD). RNase III can affect RNA structure and gene expression in either of two ways: as a dsRNA-processing enzyme that cleaves dsRNA, or as a dsRNA binding protein that binds but does not cleave dsRNA. We previously determined the endoND structure of Aquifex aeolicus RNase III (Aa-RNase III) and modeled a catalytic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
157
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(170 citation statements)
references
References 42 publications
11
157
1
1
Order By: Relevance
“…These studies also indicated that a subclass of dsRBDs prefers stem-loops over A-form RNA helices [33,35]. In some structures, a sequence-specific contact has been observed between a main-chain carbonyl of the β1-β2 loop and an amino group of a guanosine in the minor groove [32,34,36,37]. In addition, a large variety of contacts have been described between helix α1 and both regular minorgrooves [32,34,36,37] and apical loop structures [33,35,38].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…These studies also indicated that a subclass of dsRBDs prefers stem-loops over A-form RNA helices [33,35]. In some structures, a sequence-specific contact has been observed between a main-chain carbonyl of the β1-β2 loop and an amino group of a guanosine in the minor groove [32,34,36,37]. In addition, a large variety of contacts have been described between helix α1 and both regular minorgrooves [32,34,36,37] and apical loop structures [33,35,38].…”
Section: Introductionmentioning
confidence: 92%
“…The structures of different dsRBDs have been determined uncovering a mixed α/β fold with a conserved αβββα topology in which the two α-helices are packed against the three-stranded anti-parallel β-sheet [30,31]. In addition, structures of dsRBDs have been determined in complex with dsRNA, predominantly with non-natural RNA duplexes [32][33][34][35][36][37][38], revealing the canonical mode of dsRNA recognition by dsRBDs. Molecular recognition is made via three regions of interaction: helix α1 and the loop between β1 and β2 contact dsRNA minor grooves at one turn of interval whereas the short loop between β3 and α2 together with the N-terminal part of helix α2 contact the dsRNA phosphate backbone across the major groove.…”
Section: Introductionmentioning
confidence: 99%
“…Previous observations that dsRBMs bind to perfect dsRNA, in a sequence-independent manner (Schreiber et al, 1989;Ryter and Schultz, 1998;Ramos et al, 2000;Blaszczyk et al, 2004), have suggested that the dsRBMs of ADAR2 may recognize all of their RNA targets in a similar manner. Consistent with this idea, ADAR2 has been shown to nonspecifically deaminate adenosine moieties in a wide range of synthetic RNA duplexes Liu et al, 1999;Lehmann and Bass, 2000;Cho et al, 2003;Dawson et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…The lack of obvious sequence requirements for the binding of dsRBM-containing proteins led to the initial conclusion that these motifs only confer general dsRNA-binding affinity with little sequence preference, yet most of the data regarding this hypothesis focused upon model RNA substrates that contained a perfect RNA duplex (Ryter and Schultz, 1998;Ramos et al, 2000;Blaszczyk et al, 2004). By contrast, more recent studies using naturally occurring dsRNAs, formed by intramolecular base pairing between imperfect, inverted repeats, have indicated that dsRBMs have unique functional properties based upon intrinsic binding preferences and affinities (Spanggord et al, 2002;Stephens et al, 2004;Stefl et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation